PENGARUH TERAPI BERMAIN BONEKA TANGAN DAN PERPADUAN NYANYIAN (Lagu cara menggosok gigi dengan benar) TERHADAP KEMAMPUAN ANAK DALAM MELAKUKAN MENGGOSOK GIGI PADA ANAK - Homsatun Homsatun; Nur Hamim; Erna Handayani (JOURNAL SAINS STUDENT RESEARCH, 2025)
Oral and dental health is part of overall body health. Dental and oral health can reflect overall body health, including nutritional deficiencies and symptoms of other diseases. Therefore, in this case, hand puppet therapy combined with singing is necessary. This study aims to determine the effect of hand puppet therapy combined with singing on children's tooth brushing skills.This study used a single-group pretest/posttest on all 30 students who met the inclusion and exclusion criteria. The instrument used was an observation sheet for tooth brushing skills, which was edited, coded, scored, and tabulated. Data obtained in this study were analyzed using the Wilcoxon test.The results of this study revealed tooth brushing ability during the pre- post period. The results showed that the majority of tooth brushing ability before the intervention was in the poor category (14 respondents (56.7%). Meanwhile, the majority of tooth brushing ability after the intervention was in the good category (15 respondents (50%). The Wilcoxon test obtained a p-value of 0.000 (with α = <0.05, p). It can be concluded that there is an influence of hand puppet play therapy and a combination of songs (songs on how to brush teeth properly) on children's tooth brushing ability. The effect of hand puppet play therapy combined with songs can develop students' innovation and creativity. Therefore, providing hand puppet play therapy combined with songs on tooth brushing ability can be effective and enjoyable for respondents, and respondents are not burdened by the ongoing learning process.